The Impact of Regional Original Income, Balancing Funds, and Fiscal Stress on Capital Expenditures and Regional Government Financial Performance - Primadi, Fergisa Rindang; Putra, Wirmie Eka; Gowon, Muhammad (Al-Makki Publisher, 2024)
Over the last few years, the financial performance of district/city governments in Jambi province has decreased. This condition can be seen from the regional financial independence which is still very low. Therefore, this research aims to analyze more deeply the influence of local revenue, balancing funds, and fiscal stress on regional government financial performance, both direct and indirect influences through capital expenditure. This research is quantitative descriptive. The research was conducted in all districts/cities in Jambi province and used secondary data. Data was obtained through the BPK-RI Jambi Province Representative page in the form of audited regional government financial reports with an observation period from 2017-2022. The data analysis method uses the path analysis method. The study's findings demonstrate that original revenue that is largely generated locally and balancing funds have a major and favorable impact on capital spending. Capital spending is not significantly impacted by fiscal stress. The financial performance of local governments is not significantly impacted by local revenue or fiscal strain. The financial performance of local governments is significantly and negatively impacted by partly balancing funds. The financial performance of local governments is positively and significantly impacted by capital expenditures. Additionally, it was shown that capital spending might moderate the impact of balancing budgets on the financial performance of local governments. But, capital spending does not mitigate the impact of local revenue and fiscal strain on the financial performance of local governments. This research has implications for formulating policies to increase local original income, determining the allocation of capital expenditure and improving the financial performance of regional governments in districts/cities in Jambi province.